Corporate governance, internal audit quality and financial reporting quality of financial institutions - Twaha Kigongo Kaawaase; Catherine Nairuba; Brendah Akankunda; Juma Bananuka (Emerald Publishing Limited, 2021)
The purpose of this study is to establish the relationship between corporate governance attributes (board expertise, board independence and board role performance), internal audit quality and financial reporting quality using evidence from Uganda's financial institutions.This study research design is cross sectional and correlational. The study used a questionnaire survey of Chief Finance Officers, Senior Accountants and Internal audit managers of financial institutions in Uganda. Data were analyzed with the help of Statistical Package for Social Sciences.Results indicate that board expertise and board role performance are significantly associated with financial reporting quality. Also, internal audit quality is significantly associated with financial reporting quality. Board independence is not a significant predictor of financial reporting quality.This paper provides insights of what matters for financial reporting quality in Uganda's financial reporting quality. It uses the qualitative characteristics of financial statements to measure financial reporting quality. This paper focuses mainly on the conceptual framework developed by the International Accounting Standards Board.